Trade Patterns in Central America and the Dominican Republic:: Is It Time for a Competitiveness Agenda? - Maldonado, Leonardo Jose (Latin American Journal of Trade Policy, 2020)
This paper explores international trade data, classified by technology-intensiveness and type of products, to identify stylized facts, strengths, and weaknesses of the trade patterns in the region of Central America and the Dominican Republic, between 1975 and 2016. I focus the analysis not only on the total export of the region but on its exports to the United States (main trade partner). I examine export concentration, comparative advantages, trade specialization, and relative quality of the export basket (characterizing zones with high tax incentives in the region, free zones). The main findings suggest that the region has made little progress in improving trade accounts. The gains in diversification are being lost, the comparative advantages have historically remained in traditional exports, and the region does not appear to export quality to the world. The model of tax incentives is not generating local spillovers, and the relative quality of exports, as well as the specialization patterns, revive the idea of adjusting promotion schemes for local industry and direct investment. It is time for a competitiveness agenda.